Iluzija o univerzalnem dostopu do zdravstvenega zavarovanja - Lipovec Čebron, Uršula (Etnolog. Nova vrsta (Ljubljana), 2015)
The article focuses on the social changes which in our post-welfare country lead to the exclusion of a growing number of inhabitants from access to social rights. This is illustrated by the gradual reduction of rights in the health care system or, more accurately, the increasingly restricted access to health insurance in Slovenia. The latter trend is analyzed trough the changes in legislation and social and health policies, and also on the basis of a range of qualitative researches. The article first deals with the restricted access to health insurance for non-citizens, and in the following chapters for precarious workers and the poorest inhabitants of Slovenia. The authors show that their exclusion ensues through the production of the "Other" as an undeserving individual who - based on the neoliberal logic of selection - is justly denied access to these rights.
Keywords: medicine anthropology; medicinska antropologija; health insurance; zdravstveno zavarovanje; zdravstvene pravice; health rights; socialno skrbstvo; welfare state; migranti; migrants; precarious workers; prekarni delavci; revni prebivalci; poor inhabitants; Slovenia; Slovenija